2021
DOI: 10.3390/ijerph18073424
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of HIV Infection and Associated Risk Factors in Botswana

Abstract: Botswana has the third highest human immunodeficiency virus (HIV) prevalence globally, and the severity of the epidemic within the country varies considerably between the districts. This study aimed to identify clusters of HIV and associated factors among adults in Botswana. Data from the Botswana Acquired Immunodeficiency Syndrome (AIDS) Impact Survey IV (BIAS IV), a nationally representative household-based survey, were used for this study. Multivariable logistic regression and Kulldorf’s scan statistics wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Subsequently, we tracked the spatiotemporal variation in the reported HIV infection cases in Nanning by identifying centroids and their shifts. The results also showed an evident trend: the centroids of the HIV-reported case area displayed a southeast–northwest direction, specifically in Phase II of the GACP, suggesting that Nanning City might experience a diffusion of HIV outward from cities into rural areas, consistent with other countries and globally [ 23 , 30 ]. There are several possible reasons for this shift in spatiotemporal centroids.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Subsequently, we tracked the spatiotemporal variation in the reported HIV infection cases in Nanning by identifying centroids and their shifts. The results also showed an evident trend: the centroids of the HIV-reported case area displayed a southeast–northwest direction, specifically in Phase II of the GACP, suggesting that Nanning City might experience a diffusion of HIV outward from cities into rural areas, consistent with other countries and globally [ 23 , 30 ]. There are several possible reasons for this shift in spatiotemporal centroids.…”
Section: Discussionsupporting
confidence: 60%
“…Spatial cluster analysis of HIV-1 case reporting was implemented using SaTScan [ 22 ]. Statistically significant windows were evaluated using Monte Carlo simulations; the primary and secondary clusters were determined based on window likelihood values [ 23 ]. In this study, the relative risk (RR) was calculated using the observed number of individuals within the windows [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…These disparities in their psychosocial needs and the association between lack of satisfaction with services and internalizing disorders supports the need to rethink the generally practiced ‘broad-brush approach’ to health care and prevention in ALWHIV in many African settings [ 10 , 32 ]. Also, more research should focus on the benefits and proper implementation of individualized management plans that consider adolescents' peculiar factors, such as gender, MOI and other psychosocial needs since this is not being currently done.…”
Section: Discussionmentioning
confidence: 99%
“…A wide of economic and socio-cultural factors are responsible for increasing the vulnerability of African women to HIV infection [22]. Some spatial analyses of the HIV also found that HIV clusters tend to be in economically developed areas [11,13].…”
Section: Discussionmentioning
confidence: 99%